Islamic Religious Education Learning Innovation to Enhance Educational Quality - Diva, Aulia; Ulin Nuha, Nazahah (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
This study aims to examine instructional innovation in IslamicReligious Education (IRE) as a strategic approach to enhancing theoverall quality of education comprehensively. The study employeda library research approach using content analysis of variousscholarly sources, including academic books, peer-reviewedjournals, and relevant scientific articles. The conceptual frameworkwas developed based on the theories of constructivism, humanism,and active learning, all of which emphasize the active engagementof learners in the instructional process and the holistic developmentof cognitive, affective, and psychomotor domains. The findingsreveal that the implementation of innovative instructional models,such as Project-Based Learning (PjBL), Problem-Based Learning(PBL), the integration of digital technologies, and ContextualTeaching and Learning (CTL), significantly enhances students’learning motivation, deepens the internalization of Islamic values,and fosters twenty-first-century competencies, including criticalthinking, creativity, collaboration, and communication skills.However, several major challenges were identified, includinglimited educational infrastructure, inadequate teacher competencein utilizing digital technologies, and insufficient institutionalsupport. Therefore, the study recommends strengthening teachers’professional capacity through continuous training programs,providing adequate digital learning facilities, and enforcing policiesthat support sustainable educational innovation. In conclusion, thisstudy affirms that instructional innovation in Islamic ReligiousEducation constitutes a strategic pathway toward establishing aneducational system that is relevant, dynamic, and capable ofcultivating noble character and learner competencies in accordancewith contemporary societal demands.